The determinants of private investment in a mining export economy. Peru: 1997-2017 - Mendoza Bellido, Waldo; Collantes Goicochea, Erika (Pontificia Universidad Católica del Peru. Departamento de Economía, 2018)
Peru is an economy where about 60 percent of exports are mineral, of which copper, in turn, represents half. What is the weight of international factors and domestic factors in determining private investment in this mining export economy? In this paper, we identify the dominant influence of international conditions on the evolution of private investment in Peru, as well as the enormous individual weight of the price of exports in this evolution. In the period 1997-2017, external factors explained 54, 64 and 38 percent of the variance in the growth rate of total private investment, mining investment, and non-mining investment, respectively; while more than, half of the weight of external factors was explained by the price of exports. On the other hand, domestic factors explained 46, 36 and 62 percent of the variance in the growth rate of total private investment, mining investment and nonmining investment; while about 40 percent of the weight of domestic factors was explained by public investment. These findings are important because they show the price of exports to be the main channel connecting private investment in Peru with the world economy, and public investment as the most effective policy variable affecting it.

El Perú es una economía donde alrededor del 60 por ciento de las exportaciones son de minerales y la mitad de estas son de cobre. ¿Cuál es el peso de los factores internacionales y los factores domésticos en la determinación de la inversión privada en esta economía minero exportadora? En este trabajo se ha encontrado la influencia dominante de las condiciones internacionales en la evolución de la inversión privada en el Perú y el enorme peso individual del precio de las exportaciones en dicha evolución. En el periodo 1997-2017, los factores externos han explicado el 54, el 64 y el 38 por ciento de la varianza de la tasa de crecimiento de la inversión privada total, de la inversión minera y de la inversión no minera, respectivamente; y aproximadamente más de la mitad del peso de los factores externos ha estado explicada por el precio de las exportaciones. Por otro lado, los factores internos han explicado el 46, el 36 y el 62 por ciento de la varianza de la tasa de crecimiento de la inversión privada total, de la inversión minera y de la inversión no minera; y alrededor del 40 por ciento del peso de los factores domésticos ha estado explicado por la inversión pública. Estos hallazgos son importantes pues identifican al precio de las exportaciones como el principal canal que conecta la inversión privada en el Perú con la economía mundial, y a la inversión pública como la variable de política más eficaz para afectarla.
Documento de trabajo; 463
Keywords: Total private investment; Private mining investment; Non-mining private investment; Export price; Public investment; Fluctuations; Impulse-response; Variance decomposition; Historical decomposition; http://purl.org/pe-repo/ocde/ford#5.02.00